Prospective Observational Study to Compare and Validate Objective Pain Score Vs Numerical Rating Scale To Evaluate Acute Post Operative Pain - U.Monica Varshini, Mouriya S, M.Uma Maheswari, Karthik Krishnamoorthy* (Journal of Neonatal Surgery, 2025)
Background: Postoperative pain management is crucial for enhancing patient recovery, especially following major abdominal surgeries. Accurate assessment of pain is essential to administer appropriate analgesia. Traditionally, the Numerical Rating Scale (NRS) is widely used, but its subjective nature can lead to inconsistencies. The Objective Pain Score (OPS), a newer and more objective tool, may offer a more accurate assessment of acute pain. Aim: To compare and validate a 4-point Objective Pain Score (OPS) for evaluating acute postoperative pain against the Numerical Rating Scale (NRS) in patients undergoing elective laparotomy surgeries. Methods: This prospective observational study was conducted in the Post Anesthesia Care Unit (PACU) at SRM hospital over 12 months, involving 96 patients who underwent elective abdominal surgeries. Pain assessment was performed using both OPS and NRS at regular intervals for 48 hours postoperatively. Rescue analgesia was administered based on the pain scores, with paracetamol for moderate pain and fentanyl for severe pain. Discrepancies between OPS and NRS were resolved by consulting the acute pain service (APS) consultant. Results: Out of 1,824 paired OPS and NRS readings, 145 instances showed disagreement, with OPS proving more reliable in determining the need for analgesia. OPS demonstrated superiority in minimizing unnecessary administration of higher-level analgesics, particularly when NRS overestimated pain severity. Statistical analysis showed that OPS is more consistent and objective than NRS. Conclusion: The study concludes that while NRS remains a conventional pain assessment tool, OPS offers a slight advantage due to its objective nature. Implementing OPS in postoperative pain management could reduce unnecessary administration of higher-level analgesics, thus optimizing pain control.